Biologia reprodutiva do Camurupim, Megalops atlanticus, e do peixe Espada, Trichiurus lepturus, duas das principais espécies de peixes ósseos capturados no extremo oeste do Ceará, Brasil - Silva, Carlos Eduardo Lira dos Santos (2019)
The Tarpon and Cutlassfish are important species as fishing resources serving as food and source of income for the families of artisanal fishermen, besides integrating the local marine biodiversity. Research that describes the reproductive biology of these species is scarce or incomplete, especially for the Northeast region. The Tarpons were captured monthly in Bitupitá using two fishing gears: longline and fixed trap, during the period from October 2017 to September 2018. In the field were weighed, measured, identified according to the type of fishing gear used, besides the macroscopic evaluation of the gonads, fixation and conservation for microscopic analysis. A total of 252 individuals were sampled, being 150 females and 102 males. The sexual ratio was 1: 1.5 (M:F), evidencing a high dominance of females in higher length classes. Both sexes presented negative allometry. The values of IGS, K and sexual maturity indicate that the reproductive period occurs between of August and November, that is, during a dry season. The L50 presented values of 101.7 cm TL for females, 99.4 cm TL for males and 101 cm TL for the clustered sexes. The calculated mean fecundity was 7,535.815 oocytes and the species present asynchronous oocyte development and spawning in batches. Cutlassfish specimens were monthly obtained from August 2017 to July 2018 in fixed traps in Bitupitá. In Bioecologia Pesqueira laboratory (Biopesca) at the Federal University of Piauí-UFPI were weighed, measured and identified sexually. The gonads were evaluated macroscopically and later fixed and conserved for future microscopic analysis after the histological process. A total of 437 specimens were sampled, being 255 females and 182 males. The sex ratio was 1: 1.4 (M:F), with high females dominance in superior classes of lengths. Both sexes presented isometry and the same pattern was observed with the clustered sexes. The values of IGS, IHS, K and sexual maturity indicate that the reproductive period occurs between the months of August and December, that is, during the dry period. The mean fecundity estimated was 51.209 oocytes. The species presents asynchronous oocyte development and spawning in batches.